Reconstruction of chirp mass in searches for gravitational wave transients. (9th December 2015) - Tiwari, V; Klimenko, S; Necula, V; Mitselmakher, G
Abstract: The excess energy method is used in searches for gravitational waves (GWs) produced by sources with poorly modeled characteristics. It identifies GW events by searching for coincident excess energy in a GW detector network. While it is sensitive to a wide range of signal morphologies, the energy outliers can be populated by background noise events (background), thereby reducing the statistical confidence of a true signal. However, if the physics of the source is partially understood, weak model-dependent constraints can be imposed to suppress the background. This letter presents the novel idea of using the reconstructed chirp mass along with two goodness of fit parameters for suppressing background when a search is focused on GWs produced from the compact binary coalescence.